Assessment of different phytogenic-based additives on in vitro rumen fermentation profile and methane emissions - El-Zaiat, Hani M.; Masood, Hussein A.; Al Hinai, Samira S.; Al Maamari, Reem H.; Al Riyami, Sanad S.; Al-Kharousi, Kaadhia; Al-Salami, Azza H.; Al-Habsi, Nasser (Frontiers in Veterinary Science, 2025)
IntroductionPhytogenic feed additives have gained increasing attention in ruminant nutrition due to their capacity to modulate ruminal fermentation and reduce methane (CH4) emissions. This study evaluated the effects of three plant-based additives.MethodsNeem leaf (Azadirachta indica; NL), Indigofera leaf (Indigofera oblongifolia; IL), and Pumpkin peel (Cucurbita pepo; PP) included at four levels (0, 10, 20, and 30 g/kg DM) on in vitro ruminal fermentation, feed degradability, and CH4 emissions. A total mixed ration (TMR) was incubated with each additive and buffered rumen fluid using the in vitro gas production technique for 24 hours.Results and discussionNL and IL supplementation significantly (p < 0.05) increased gas and carbon dioxide (CO2) production, organic matter degradability, and total volatile fatty acid concentrations, particularly propionate and butyrate. Simultaneously, acetate concentration, CH4 emissions, NH3-N levels, and protozoa abundance were reduced (p < 0.05). However, PP had limited effects on these parameters. The phenolic profiles of NL and IL, notably rich in 2-hydroxycinnamic acid and p-coumaric acid, likely contributed to these outcomes. In conclusion, these findings support the use of NL and IL as effective phytogenic additives for improving rumen fermentation and mitigating CH4 production. Further in vivo trials are recommended to validate these in vitro results.